2014
DOI: 10.1093/jnci/dju082
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance–Guided Focused Ultrasound for Patients With Painful Bone Metastases: Phase III Trial Results

Abstract: BackgroundPain due to bone metastases is a common cause of cancer-related morbidity, with few options available for patients refractory to medical therapies and who do not respond to radiation therapy. This study assessed the safety and efficacy of magnetic resonance-guided focused ultrasound surgery (MRgFUS), a noninvasive method of thermal tissue ablation for palliation of pain due to bone metastases.MethodsPatients with painful bone metastases were randomly assigned 3:1 to receive MRgFUS sonication or place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
189
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 203 publications
(194 citation statements)
references
References 24 publications
3
189
1
1
Order By: Relevance
“…In order to quantify its use, a morphine equivalent daily dose (MEDD) intake form was used in some studies [43]. In the case of metastatic tumors, both pain scales and MEDD followed the standards published by the International Bone Metastases Consensus Working Party (IBMCWP) [44].…”
Section: Pain Palliationmentioning
confidence: 99%
“…In order to quantify its use, a morphine equivalent daily dose (MEDD) intake form was used in some studies [43]. In the case of metastatic tumors, both pain scales and MEDD followed the standards published by the International Bone Metastases Consensus Working Party (IBMCWP) [44].…”
Section: Pain Palliationmentioning
confidence: 99%
“…Prospective, single-arm multicenter trials have shown RFA and cryoablation to be safe and highly effective for treatment of symptomatic skeletal metastases [12][13][14][15][16]. A large randomized, controlled, multicenter phase III trial has shown Focused Ultrasound (FUS) to be effective in the treatment of painful bone metastases [17], confirming results of earlier retrospective reports [18]. Small case series also support benefit from other percutaneous methods of image-guided ablation, including microwave ablation, laser ablation, and irreversible electroporation to treat skeletal metastases, although the data are more limited [19][20][21][22][23][24][25][26].…”
Section: Resultsmentioning
confidence: 99%
“…75 MRgFUS has been first proposed with a potential in pain palliation of bone metastases, for its good results in patients non-responding to radiotherapy while applying acoustic energy on the bone surface resulting in bone cortex heating, and indirectly ablating the adjacent periosteum-the most innervated component of mature bone tissue, and tumour tissue, and a major source of pain. 11,76 The bone is a common site for metastasis. The primary cancers that most frequently metastasize to bone are breast and prostate cancers (post-mortem incidence of bone metastases: breast 73%, prostate 68%, thyroid 42%, lung 36%, renal 35%), and these are among the most incident and curable worldwide.…”
Section: Mrgfus Target and Applications In Musculoskeletal Pathologymentioning
confidence: 99%
“…This study demonstrated that MRgFUS is a non-invasive and safe treatment in painful bone metastases for patients in whom standard treatments have failed. 11 Recently, an article published by an international consensus held at the Focused Ultrasound Therapy Second European Symposium in Rome (2013), Italy, focused on the point about current treatment goals, current indications, technical considerations, future directions including research priorities, and economic and logistical considerations. 84 A…”
Section: Mrgfus Target and Applications In Musculoskeletal Pathologymentioning
confidence: 99%